Averting Tragedy: An Exploration of Thwarted Mass Public Shootings Relative to Completed Attacks - Rocque, Michael (Criminal justice review, 2023)
Scholarship on mass public shootings has increased in recent years as comprehensive datasets have become more available. As a result, much is known about the contextual and offender related characteristics of such attacks. However, less research has been conducted on attacks that were planned but ultimately did not occur. Understanding how mass public shootings may be thwarted or averted is important for both policy and theoretical reasons. In this paper, we describe a new dataset of averted mass public shooting threats (N = 194) from 2000–2019 and compare them to mass public shootings that were completed during this time (N = 97). Several noteworthy findings emerged, including that nearly half of the averted cases were reported by a friend or acquaintance, most targeted a specific location or group, and averted cases were more likely to involve school targets and co-offenders. Implications are discussed.